The Anthelmintic Activity of Nepeta racemosa Lam. Against Gastrointestinal Nematodes of Sheep: Rosmarinic Acid Quantification and In Silico Tubulin-Binding Studies - Büşra Karpuz Ağören; Mahmut Sinan Erez; Esma Kozan; Aydın Dağyaran; Mevlüt Akdağ; Eduardo Sobarzo-Sánchez; Esra Küpeli Akkol (Pathogens)
Gastrointestinal nematodes (GINs) inflict significant economic losses on sheep and goat farming globally due to reduced productivity and the development of anthelmintic resistance. Sustainable control strategies are urgently needed including the exploration of medicinal plants as safer alternatives to chemical anthelmintics. This genus of plants is used for anti-inflammatory, antioxidant, and antimicrobial activities. In this study, we aimed to evaluate the anthelmintic activities of Nepeta racemosa Lam. MeOH extract, n-hexane, dichloromethane (DCM), ethyl acetate (EtOAc), n-buthanol (n-BuOH) and aqueous (H2O) subextracts, and quantify rosmarinic acid in the active extract by the HPLC method, and perform in silico molecular docking studies of rosmarinic acid to examine its binding interactions with tubulin. The anthelmintic activity of the plant extracts on gastrointestinal nematode eggs and larvae (L3) of the sheep was assessed using in vitro test methods such as the egg hatch assay and larval motility assay, conducted over a 24 h period (1, 2, 3, 4, 6, 8, 24). All extracts exhibited 100% effectiveness in the egg hatch inhibition assay, regardless of concentration (50–1.5625 mg/mL). The EtOAc subextract shows the highest effectiveness at 79.66%, followed by the MeOH extract at 74.00%, water at 64.00%, n-hexane at 67.00%, and DCM at 61.00%, and the lowest effectiveness is observed with n-BuOH at 51.66% in the larval motility assay. The major compound of EtOAc extract, the most active extract of N. racemosa, was determined as rosmarinic acid and its amount in the extract was determined as 14.50 mg/100 mg dry extract. The amount of rosmarinic acid in the MeOH extract was found to be 0.21 mg/100 mg dry extract. n-Hexane, DCM, n-BuOH, and H2O extracts’ rosmarinic acid content was lower than the LOQ value. As tubulin plays an important role in the mechanism of anthelmintics, the major compound of the most active extract (NR-EtOAc) rosmarinic acid was docked onto the colchicine-binding site of the tubulin (5OV7) protein. Rosmarinic acid showed a similar activity spectrum to the anthelmintic drug albendazole. The discovery of low-cost and low-toxicity anthelmintic compounds is very important.